Can multi-stakeholder forums mediate indigenous rights and development priorities? Insights from the Peruvian Amazon - Rodríguez, D.; Sarmiento Barletti, J.P. (2021)
The protection of indigenous peoples in isolation and initial contact (PIACI) is one of the most complex issues in the human rights and environmental agenda. The implementation of frameworks to protect PIACI involves addressing conflicts by the advance of public and private initiatives and interests in their territories. This article focuses on PIACI Roundtable, a multi-stakeholder forum (MSF) established in Peru’s Loreto region to contribute to protecting these groups. The MSF sought to address the long-standing delays in the creation of five Indigenous Reserves for PIACI in Loreto’s forests. The article argues that MSFs may be fruitful spaces to raise awareness of the rights of vulnerable peoples and coordinate the implementation of supporting actions, but only when participants hold a shared respect for those recognised rights. If not, MSFs may become spaces where powerful actors relegate recognised rights to a perspective among others.